TACTIP - Tactile fingertip device, challenges in reduction of size to ready for robot hand integration - Winstone, Benjamin; Griffiths, Gareth; Melhuish, Chris; Pipe, Tony; Rossiter, Jonathan (2012 IEEE International Conference on Robotics and Biomimetics, 2012)
Previous work on the TACTIP project has demonstrated a prototype tactile fingertip device, at a little over twice the diameter(40mm) of a human fingertip (16-20mm). Unlike most other developed MEMS sensors, the TACTIP device is appropriate for all tasks for which humans use their fingertips; examples include object manipulation, contact sensing, pressure sensing and shear force detection. This is achieved whilst maintaining a very high level of robustness. Further work with this concept has reduced the size of the device to that closely matching the range of a human fingertip (20mm). Previous development of the TACTIP device has in isolation, proven the potential for these applications, but not provided a benchmark specification of its technical performance. This paper presents benchmarking results from testing pressure and shear force readings using both versions of the TACTIP designs with comparisons that highlight the compromises encountered when reducing the physical build size of the device. The results show that a reduced size device offers greater sensitivity under lower forces, but cannot be subjected to the greater forces that the larger device can.